Penanganan Epilepsi Grand Mal Sebagai Akibat dari Ketidaknormalan Kerja Neuron di Otak Menggunakan Metode Diet Ketogenik - Nommensen Pangihutan Ompusunggu; Sabar Manampin Giawa; Wahyu Irawati (BIOEDUSCIENCE, 2022)
Background: The nervous system is composed of a complex structure to support its highly organized work. Damage to the working mechanism of nervous systems can exert fatal impacts to the human body. One of the consequences of damage to the mechanism of action potentials is grand mal epilepsy. The purpose of this paper is to determine the structure, function, and mechanism of action of neurons, establish grand mal epilepsy as a result of damage to the working mechanism of neurons, and recognize the ketogenic diet as a non-pharmacological therapy for epilepsy patients. Methods: The research method used is descriptive qualitative research. Results: Nerve cells generally consist of dendrites for receiving stimuli, cell bodies for transmitting stimuli to the axon, and axons for transmitting stimuli to other nerve cells. Grand mal epilepsy is a nervous system disorder caused by the increased activity of sending electrical waves throughout the brain that can reach up to four times faster than normal. However, grand mal epilepsy patients suffer from an excessive number of seizures that may occur at any time. Conclusions: The ketogenic diet method is a high-fat and low-carbohydrate diet method that can reduce electrical activity in the brain. Ketone-containing fats have a stabilizing effect on the central nervous system, contributing to anticonvulsant and antiepileptic effects that may reduce the excessive number of seizures experienced by patients. The application of this diet should be balanced with the provision of additional intake of multivitamins, minerals, and fiber to balance the nutrients the body needs.